High-Temperature Oxidation Behavior of a Cu-Bearing 17Cr Ferritic Stainless Steel - Zhang, Mengqi (Scanning, 2020)
The isothermal oxidation behavior of 17Cr-0.85Si-0.5Nb-1.2Cu ferritic stainless steel in air was studied from 850°C to 1050°C by analyzing its weight gain after oxidation. The kinetic curves were plotted using the oxidation weight-gain data, and the structure, surface morphology, and element distribution of the oxide films were analyzed by XRD, SEM, and EDS. The results showed that the oxidation kinetics curves at 850°C and 950°C followed a parabolic law, and a continuous and dense oxide film composed of Cr(2)O(3) and MnCr(2)O(4), FeCr(2)O(4), and Cu-Cr rich spinel was formed, which reveals that the steel displayed good oxidation resistance. When the temperature was increased to 1050°C, the oxidation kinetics curves gradually changed from parabolic to linear after 40 h exposure, which indicated that the oxidation resistance significantly worsened. A lower oxidation resistance was observed at 1050°C due to the formation of a large amount of Fe(2)O(3) on the surface and the volatilization of the inner Cr(2)O(3) layer.